Revitalization of the Office of Religious Affairs (KUA): Between the Hope for Improved Services and the Reality of Infrastructure Gaps) - Yeni Syamyuliati (AMUYA: JOURNAL OF MANAGEMENT, 2025)
This policy paper analyzes the inaccurate targeting of the Ministry of Religious Affairs' (KUA) revitalization program, characterized by a gap between the massive physical infrastructure development and the stagnant quality of public services. This problem is rooted in three main causes: (1) limited data and accurate field information; (2) the absence of a strict data verification and validation policy; and (3) the absence of a sustainable evaluation mechanism. Although the program aims to create modern services, funding allocation decisions are often based on invalid reports, political lobbying, or irrelevant criteria, resulting in many KUAs that actually need improvement being neglected. This paper uses qualitative methods with a descriptive analysis approach and literature study. Data were collected through literature review and analysis of relevant documents, including laws and regulations, government reports, and scholarly articles related to public policy and KUA revitalization. The conceptual foundation of this research is supported by the Theory of Bounded Rationality, Agency Theory, and Management Information System Theory to identify and diagnose the root of the problem. The results of this study recommend shifting the policy focus from an input-output orientation to an outcome orientation, with a priority on developing an integrated information system and establishing independent data verification as the primary solution. It is hoped that these recommendations can provide input for the Ministry of Religious Affairs in creating a more effective, accountable, and targeted revitalization program.